ANALISIS KESENJANGAN PENDAPATAN ANTAR KABUPATEN/KOTA DALAM PROVINSI ACEH - Mahrizal, Abubakar Hamzah, Sofyan Syahnur. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract: Growing income gap has led to various problems such as rising unemployment, lack of health and education, housing, basic needs and security. So that the author wishes researching on the development of economic growth and development of the population that influence the income gap among districts / cities in Aceh province. Location of the research conducted in the province of Aceh, using secondary data obtained from the office of the Central Bureau of Statistics Aceh. For purposes of analysis used modeling approaches Williamson index and convergence analysis results showed that the disparity of per capita GDP among the districts / cities in Aceh province during the period 2002-2011 has the highest value of 0.839 and the lowest 0.747 Aceh province including high level of inequality criterion. Trend GDP per capita disparity continues to decline but are fluctuations from year to year. By looking at the convergence coefficient beta = 0.0637 which is positive, confirms that there has been a divergence rather than convergence occurs in GRDP per capita disparities between districts / cities in Aceh province. Based on the results of research that has been done, then the need is to reduce the gap and seek to create konvegensi through the efforts of physical development and human resources equally on each district / city in order to overcome the development gap . Keywords: GDP and Population. Abstrak: Kesenjangan pendapatan yang semakin besar telah menimbulkan berbagai masalah seperti meningkatnya pengangguran, kurangnya sarana kesehatan dan pendidikan, perumahan, kebutuhan pokok dan rasa aman. Sehingga penulis berkeinginan meneliti mengenai perkembangan pertumbuhan ekonomi dan perkembangan penduduk yang mempengarui kesenjangan pendapatan antar kabupaten/kota di Provinsi Aceh. Lokasi penelitian dilakukan di Provinsi Aceh, dengan menggunakan data skunder yang diperoleh dari kantor Badan Pusat Statistik Aceh. Untuk keperluan analisis digunakan pendekatan model Indeks Williamson dan analisis konvergensi Hasil penelitian menunjukkan bahwa Disparitas PDRB Per Kapita antar kabupaten/ kota di Provinsi Aceh selama kurun waktu 2002-2011 memiliki nilai tertinggi sebesar 0,839 dan terendah 0,747 maka Provinsi Aceh termasuk kriteria ketimpangan taraf tinggi. Trend disparitas PDRB per kapita terus menurun namun secara fluktuasi dari tahun ke tahun. Dengan melihat koefisien konvergensi beta = 0,0637 yang bernilai positif, menegaskan bahwa telah terjadi divergensi bukannya terjadi konvergensi dalam disparitas PDRB per kapita antar kabupaten/kota di Provinsi Aceh. Bedasarkan hasil penelitian yang telah dilakukan, maka yang perlu adalah memperkecil kesenjangan dan berupaya menciptakan konvegensi melalui upaya pembangunan fisik dan sumber daya manusia yang merata disetiap kabupaten/kota guna mengatasi kesenjangan pembangunan. Kata Kunci: PDRB dan Jumlah Penduduk.